The Flavonoid Quercetin Induces AP-1 Activation in FRTL-5 Thyroid Cells - Cesidio Giuliani (MDPI AG, 2019)
Previous studies have shown that quercetin inhibits thyroid function both in vitro and in vivo. An attempt to evaluate the effect of quercetin at the promoter level of the thyroid-specific genes led to the observation that this compound induces the basal activity of the reporter vector. Therefore, the action of quercetin has been evaluated on the basal activity of several reporter vectors: The PGL3 basic, promoter and control vectors from Promega, and a pSV-based chloramphenicol acetyltransferase (CAT) reporter vector. In the Fisher Rat Thyroid cell Line FRTL-5 thyroid cells transiently transfected, quercetin 10 μM increased the basal activity of all the reporter vectors evaluated, although the degree of the effect was significantly different among them. The analysis of the difference among the regulatory regions of these vectors identified the activator protein 1 (AP-1) binding site as one of the potential sites involved in the quercetin effect. Electromobility shift assay experiments showed that the treatment with quercetin induced the binding of a protein complex to an oligonucleotide containing the AP-1 consensus binding site. This is the first study showing an effect of quercetin on AP-1 activity in thyroid cells. Further studies are in progress to understand the role of AP-1 activation in the effects of quercetin on thyroid function.